Women in family farming: Evidence from a qualitative study in two Portuguese inner regions - Gomes, Diana; Jesus, Miguel; Rosa, Rosário; Bandeira, Cristina; Costa, Cristina Amaro da (Frontiers in Sociology, 2022)
The importance of family farming in food systems worldwide is recognized by different international bodies, as well as the leading role played by women and the inequalities they face in this sector of activity. The most recent data from Portugal highlight the importance of this type of agriculture in this Southern European country. In 2019, 68% of the total agricultural workforce in the country was concentrated in family farming, with almost half of them being women. This high permanence of women in agriculture is the result of a long process of feminization on this sector that is similar to other contexts. Despite this strong feminization of family farming, there are few studies that portrait agricultural activity from the women's viewpoint, since the voice of men is always predominant in all references. Based on the exploratory qualitative data from two focus groups, carried out in two Portuguese inner regions, we intend to address the perceptions and meanings of a small group of women farmers regarding their activity, the role taken by them in agriculture and the difficulties they experience. Issues such as changes in agriculture and the sexual division of labor will also be addressed in this article. Within these groups, women work in agriculture is perceived as long, solitary and uncertain. Also, the public/private dichotomy is evident, with decision-making and public places dominated by men. A prevalence of the discourse of “masculinization” still exists with certain tasks being attributed to men (e.g., operations with machinery). Younger women (34 and 40 years old) tend to overcome these gender differences choosing agriculture as a profession and healthy and sustainable life for their families.